The Impact of Economic Crises on the Performance of Non-Financial Corporations in the Czech Republic - Hronova, Stanislava; Hindls, Richard (International Journal of Applied Economics, Finance and Accounting, 2022)
Since the 1990s, the Czech economy has faced four crises. Each of them had different causes, duration and consequences for the non-financial corporate sector. The first crisis (1997-1998) had internal causes and severely affected non-financial firms. In contrast, the second crisis (2009) had external economic causes and non-financial corporations emerged with a positive economic outcome. As a result of extremely rigorous economic policies and net borrowing by non- financial firms, the Czech economy experienced a crisis in 2012 and 2013. The COVID- 19 pandemic was the external, not economic cause of the fourth crisis (2020-2021) that brought about a successful outcome for non-financial corporations. The aim of this analysis is to answer the question of what causes these divergent economic results and why the external impulses of the crisis led to a reversal of the traditionally negative economic balance. The results showed that the levels of indebtedness and profitability conceal the main differences in conditions. The analysis is based on data from the Czech National Accounts and uses relative indicators to describe the economic behaviour of non-financial corporations constructed in such a way that their explanatory power is closer to the conditions for assessing economic performance in corporate practice.